Increased complementarity in water‐limited environments in Scots pine and European beech mixtures under climate change. Issue 2 (25th January 2017) - González de Andrés, Ester; Seely, Brad; Blanco, Juan A.; Imbert, J. Bosco; Lo, Yueh‐Hsin; Castillo, Federico J.
Abstract: Management of mixedwoods is advocated as an effective adaptation strategy to increase ecosystem resiliency in the context of climate change. Although mixedwoods have been shown to have greater resource use efficiency relative to pure stands, considerable uncertainty remains with respect to the underlying ecological processes. We explored species interactions in Scots pine/European beech mixedwoods with the process‐based model FORECAST Climate. The model was calibrated for two contrasting forests in the southwestern Pyrenees (northern Spain): a wet Mediterranean site at 625 m.a.s.l. and a subalpine site at 1335 m.a.s.l. Predicted mixedwood yield was higher than that for beech stands but lower than pine stands. When simulating climate change, mixedwood yield was reduced at the Mediterranean site (−33%) but increased at the subalpine site (+11%). Interaction effects were enhanced as stands developed. Complementarity dominated the Mediterranean stand but neutral or net competition dominated the subalpine stand, which had higher stand density and water availability. Reduced water demand and consumption, increased canopy interception, and improved water‐use efficiency in mixtures compared to beech stands, suggest a release of beech intraspecific competition. Beech also facilitated pine growth through better litter quality, nonsymbiotic nitrogen fixation, and above‐ and belowground stratification, leading to higher foliar nitrogen content and deeper canopies in pines. In conclusion, mixtures may improve water availability and use efficiency for beech and light interception for pine, the main limiting factors for each species, respectively. Encouraging pine–beech mixtures could be an effective adaptation to climate change in drought‐prone sites in the Mediterranean region.